Power plant performance and efficiency analysis - Ling, Teik Win (2010)
For every power plant owners and operators in operation throughout the world, plant performance, reliability, efficiency and availability are a major concern. Even though preventive measures are implemented to make sure these targets remain high but unfortunately, these problems cannot be eliminated entirely and will continue to take place unpredictably. For large power generation industry such as the Independent Power Producers in Malaysia, due to the competitive nature of business it is of utmost important to make sure the plants are always available, high performance and efficiency, less forced outages and always ready to serve the customer whenever the needs arise. Unavailability, any forced outages and low performance and efficiency of the units will severely affect the overall business operation and profitability of the company. The consequences of this will be great to the extent that sometimes will cause the company involved to wind up the operation and close the business. The impact of such incidents can be minimized if power plant operators are equipped with the relevant skills, knowledge, methodologies and suitable tools to evaluate the cause and source of these problems and at the same time, take remedy to rectify the problems and make sure it will not recur in the future. This study will focus on the improvements of performance and efficiency for the generating unit. The factors that will have effects on the plant performance are deliberated in details. Methodologies and testing related to determination of plant performance and efficiency will also be discussed. In this report, we will focus solely on the combined cycle gas turbine configuration utilizing fuel gas for electricity generation. The main tool to be used for this research is Plant Information (PI) historian system whereby we can extract the important plant parameters related to unit performance and efficiency in order to carry out the study. All the plant parameters and data to be kept in the PI system for a period of 5 years and with this, we can track the plant performance from time to time to see if there is any improvement or degradation to the performance of the unit.